Evaluasi Pendidikan Menuju Insan Kamil dalam Perspektif Filsafat Ilmu - Ujang Natadireja; Kun Nurachadijat (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2023)
This article aims to explore the methods for conducting a thorough assessment using a scientific philosophical approach. Given that inconsistencies in educational assessment practices can yield suboptimal outcomes upon examination, it becomes imperative to employ appropriate techniques for a comprehensive review. The author has crafted this article using a research approach, gathering source materials from various repositories including library books, research reports, newspapers, books, theses, dissertations, and both printed and digital scientific journals. In the context of Islamic education, the objective of evaluation is to nurture al-Insan al-Kamil, or a well-rounded human being. Similarly, the primary goal of education is to instill faith, foster piety, cultivate a religious mindset, impart knowledge, and encourage the application of acquired knowledge in adapting to broader community life. Evaluation also serves as a means to furnish students with feedback regarding their accomplishments, as well as the depth of their perspectives and knowledge acquired throughout the learning journey. Furthermore, philosophy plays a pivotal role in educating individuals to think critically, gain insights, and reason comprehensively, enabling them to approach events or problems from multiple angles and ultimately arrive at correct solutions.